Analisis Instruksional Mata Pelajaran Bahasa Inggris pada jenjang SMP dalam Meningkatkan Kemampuan Berbahasa Inggris Siswa - noviar, Anggi; Herdiana, Dodi (Journal of Education, 2024)
ABSTRACT Instructional analysis is a process for studying and evaluating a learning process. Instructive analysis can be performed for a variety of subjects, including English for middle school. The purpose of this instructional analytics is to determine the effectiveness of the English language learning process for junior high and junior high. This instructive analysis is carried out using qualitative descriptive methods. The data collected is observation data, interviews, and documentation. The results of the analysis showed that the process of learning English in the 9th grade was not fully effective. This is evidenced by a number of factors, including: (1) excessive and dense content; (2) less varied learning methods; (3) insufficient learning facilities; and (4) a lack of student learning motivation. Based on the results of the analysis, it is recommended that teachers of English for secondary and secondary education in the ninth grade do some of the following: (1) simplify the lesson material; (2) use more varied methods of learning; (3) improve the learning facility; and (4) improve student learning motivation. Keywords: instructional analysis, English, Grade IX